2020
DOI: 10.1021/acsomega.0c04307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfide Solid Electrolytes through the Liquid Phase: Optimization of the Preparation Conditions

Abstract: All-solid-state lithium batteries using inorganic sulfide solid electrolytes have good safety properties and high rate capabilities as expected for a next-generation battery. Presently, conventional preparation methods such as mechanical milling and/or solid-phase synthesis need a long time to provide a small amount of the product, and they have difficult in supplying a sufficient amount to meet the demand. Hence, liquid-phase synthesis methods have been developed for large-scale synthesis. However, the ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…The scattering data were collected in terms of background, absorption, multiple scattering, and inelastic scattering. The calculations were performed according to previous studies, as follows. The structure factor, S ( Q ), was obtained by standardization of the collected scattering data using the number of atoms and scattering intensity of one atom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering data were collected in terms of background, absorption, multiple scattering, and inelastic scattering. The calculations were performed according to previous studies, as follows. The structure factor, S ( Q ), was obtained by standardization of the collected scattering data using the number of atoms and scattering intensity of one atom.…”
Section: Methodsmentioning
confidence: 99%
“…Along with many efforts to clarify the origin of the low ionic conductivity of Li 3 PS 4 , we had previously investigated the cause of the low ionic conductivity of solid electrolytes prepared by liquid-phase synthesis through the pair distribution function (PDF) analysis, which was known as a suitable tool for the analysis of amorphous materials. It was found that thermal treatment to remove the remaining solvents under a vacuum led to an increase in crystallinity with a decrease in ionic conductivity. Furthermore, we demonstrated that ionic conductivity can be improved by modifying the annealing conditions for the electrolyte synthesized by the liquid-phase synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] This pioneering work, showing an easily scalable synthesis method, opened up the prospect for the mass production of solid electrolytes. [ 7–9 ] It is to mention that this route is also the first step in the solvent‐mediated synthesis of argyrodites (Li 6 PS 5 X), another solid electrolyte family in the spotlight for practical all‐solid state batteries. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…A recent work suggests that Li2S residual which cannot be detected by XRD decreases the ionic conductivity of synthesized electrolytes. 38 Thus, further improvement of the conductivity may be achieved by complete the synthesis reaction. As P2S5 dissolves in anisole at high temperatures (Figure S6), it is considered that dissolved P2S5 is involved in the reaction.…”
Section: Synthesis Of Solid Electrolytes: Suspension and Solutionmentioning
confidence: 99%